An Android Attendance Solution for Eco-Campus Life. - Aslina Baharum; Nordaliela Mohd Rusli; Mohd Helmy Abd Wahab; Nur Shahida Ab Fatah; Nurhafizah Moziyana Mohd Yusop; Wong, Kai Jie (2019)
In UMS, signing attendance is very inefficient. Usually the signing of attendance starts when the lecturer gives out the attendance sheet in the lecture hall. If class is huge, it will take almost the whole lecture time to complete the process. The method used in UMS for signing attendance is basically passing the attendance sheet around. This will not only distract the class, it will also cause someone to miss the attendance sheet because of the passing process is not consistent. There is also potential of data loss due to human’s mistake such as misplacing the attendance sheet. In order to solve these problems, this project proposed an Android-based application integrated with a web application to make the process of recording attendance more efficient. The objectives for this project are to develop Android-based application with interface for students to record attendance as well as another interface, which allows lecturers to track the students’ attendance. The database for the content management system was developed to integrate with the Android Attendance Solution (AAS). The expected outcome for this project would be a fully functional attendance recording application. With this application, the whole process of recording attendance can be made easier and thus saves time as well as resources such as pen and paper.